2023
DOI: 10.3389/fpubh.2023.1241388
|View full text |Cite
|
Sign up to set email alerts
|

Deep-learning model for predicting physical fitness in possible sarcopenia: analysis of the Korean physical fitness award from 2010 to 2023

Abstract: IntroductionPhysical fitness is regarded as a significant indicator of sarcopenia. This study aimed to develop and evaluate a deep-learning model for predicting the decline in physical fitness due to sarcopenia in individuals with potential sarcopenia.MethodsThis study used the 2010–2023 Korean National Physical Fitness Award data. The data comprised exercise- and health-related measurements in Koreans aged >65 years and included body composition and physical fitness variables. Appendicular muscle mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Possible SO prevalence was higher among women than among men, suggesting that sarcopenia and SO in women were associated with an increased all-cause mortality risk independent of obesity, although this association was not significant in men 50 . Lower BF levels were reported in women with sarcopenia in a previous study, and our finding of a high BF level was related to possible SO 32 , 51 . The probability of possible SO had the highest feature importance factor of BF because obese adipose tissue inflammation dominates skeletal muscle inflammation, leading to SO, which is exacerbated by the age-related decline in muscle mass and function 52 .…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Possible SO prevalence was higher among women than among men, suggesting that sarcopenia and SO in women were associated with an increased all-cause mortality risk independent of obesity, although this association was not significant in men 50 . Lower BF levels were reported in women with sarcopenia in a previous study, and our finding of a high BF level was related to possible SO 32 , 51 . The probability of possible SO had the highest feature importance factor of BF because obese adipose tissue inflammation dominates skeletal muscle inflammation, leading to SO, which is exacerbated by the age-related decline in muscle mass and function 52 .…”
Section: Discussionsupporting
confidence: 68%
“…The possibility of low grip strength was associated with elevated levels of pro-inflammatory cytokines, which decreased muscle strength and developed SO 55 . Using the same dataset as the Korean National Physical Fitness Award between 2010 and 2023, the sequential deep learning model showed that absolute grip strength was the most important factor for predicting possible sarcopenia in older adults 32 . The results of the deep learning model had high accuracy (AUCRC = 0.95) and recall with possible sarcopenia, and our results also showed that the possible SO prediction model had a high accuracy of performance (AUCRC = 0.97).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations